Strategi Meraih Ceruk Pasar di Era New Normal (Studi Kasus pada Hotel Santika Pekalongan) - Siti Nurhayati; Wenty Ayu Sunarjo; Dwi Susilo (Jurnal Ekonomi dan Bisnis, 2022)
Since the Covid-19 pandemic was announced by the World Health Organization (WHO) on March 11, 2019, this has caused many economic shocks, both at the individual, household and company scale, as well as affecting the economy of a country and the world. One of the activities that has been significantly affected is hospitality. More than 3 months since the onset of Covid-19, hotels have barely received customers, occupancy is almost empty, and many employees are laid off. The aim of this research is to increase consumer confidence in Hotel Santika's services by implementing health protocols in marketing their products through service innovation, creation of excellence, and the strength of their offerings. The approach method used is descriptive statistics with multiple regression analysis tools. The results of this study are that there is one variable that has a negative influence on purchasing decisions (product innovation), while the other three variables (Promotion, Offering Power, and Online Media Utilization) have a positive influence on purchasing decisions